Data for: Numerical Investigation of Oleo-Pneumatic Shock Absorber: A Multi-Fidelity Approach - Sheikh Al Shabab, Ahmed; Grenko, Bojan; Vitlaris, Dimitrios; Tsoutsanis, Panagiotis; Antoniadis, Antonios; Skote, Martin (Cranfield University, 2023)
Raw data of simulations used in the ECCOMAS 2022 paper titled Numerical Investigation of Oleo-Pneumatic Shock Absorber: A Multi-Fidelity Approach
Keywords: Shock Absorbers; 'Turbulence'; 'Multiphase'; 'Multifidelity'